Thermo oxidative degradation behavior of jatropha curcass L. oil in the presence of antioxidant - Syah Lubis, A.M.H. (2013)
Seed oils were used as base oil since long time ago. However their usage is limited due to its thermo oxidative and cold flow properties. Chemical modification and addition of proper additives are known to be able to improve these limitations. In this work, the effect of octadecyl 3- (3,5-di-tert-butyl-4-hydroxyphenyl) propionate as potential hindered phenol antioxidant (HPAO) on thermo-oxidative degradation of jatropha oil was investigated. 1, 3, 5 wt of antioxidant was dissolved into jatropha oil and their thermo-oxidative behavior was studied by using thermogravimetric analysis method under oxidative environment. The addition of the HPAO was found to accelerate the occurrence of thermal degradation first onset of jatropha oil. This factor corresponds to reaction of the compound during heating that reduces the peroxides formation to a less-reactive alcohol which is more volatile, thus making the first onset temperature occurred at a lower temperature. Â© (2013) Trans Tech Publications, Switzerland.